The effect of infant-directed speech on early multimodal communicative production in Spanish and Basque. Issue 2 (20th March 2020) - DE PABLO, Irati; MURILLO, Eva; ROMERO, Asier
Abstract: We analyzed the effect of infant-directed speech (IDS) on multimodal communicative production of children at the beginning of the second year of life in two different languages: Spanish and Basque. Twelve Spanish and twelve Basque children aged between 12 and 15 months observed two versions of an audiovisual story: one version was narrated with IDS and the other with adult-directed speech (ADS). We analyzed the use of gaze and the communicative behaviors produced by children. The time spent looking at the story increases in the IDS condition regardless of the language of the narration. Children produced more multimodal communicative behaviors while watching the IDS version both in Spanish and in Basque. These results suggest that IDS increases attention and social engagement promoting joint attention episodes.